2015
DOI: 10.1007/jhep11(2015)069
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative U(1) gauge theory from a worldline perspective

Abstract: We study pure noncommutative U(1) gauge theory representing its one-loop effective action in terms of a phase space worldline path integral. We write the quadratic action using the background field method to keep explicit gauge invariance, and then employ the worldline formalism to write the one-loop effective action, singling out UV-divergent parts and finite (planar and non-planar) parts, and study renormalization properties of the theory. This amounts to employ worldline Feynman rules for the phase space pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A common starting point in such a setting is the introduction of the fundamental commutator between spatial coordinates x i ,x j = iθ i j (1) for constant non-commutativity parameters assembled into a real, skew-symmetric matrix θ i j . Much progress has been made in understanding various aspects of these noncommutative spaces [5] and their application to quantum a e-mail: jedwards@ifm.umich.mx field theory [6][7][8][9], where the effects of UV / IR mixing have played an important rôle. There is also interest in generalisations of (1), perhaps most famously to describe the "fuzzy sphere" [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A common starting point in such a setting is the introduction of the fundamental commutator between spatial coordinates x i ,x j = iθ i j (1) for constant non-commutativity parameters assembled into a real, skew-symmetric matrix θ i j . Much progress has been made in understanding various aspects of these noncommutative spaces [5] and their application to quantum a e-mail: jedwards@ifm.umich.mx field theory [6][7][8][9], where the effects of UV / IR mixing have played an important rôle. There is also interest in generalisations of (1), perhaps most famously to describe the "fuzzy sphere" [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…is given by a transition amplitude x|e −T δ 2 S ghost |x which can be computed in terms of a phase-space {x(t), p(t)} path integral of a particle on the circle [10,12] with Hamiltonian δ 2 S ghost . The symbol tr in (2.27) denotes the trace over the color indices in δ 2 S ghost .…”
Section: Heat-trace Representation In the Worldline Formalismmentioning
confidence: 99%
“…Indeed, it has been shown that non-commutative field theories are linked to phase-space worldline path integrals. This was developped in [10,11] for (complex-) scalar field theories and in [12,13] for a U(1) gauge theory.…”
Section: Introductionmentioning
confidence: 99%
“…Its origins can be traced to Feynman [6], with a revival of interest following Bern and Kosower's Master Formulae for field theory amplitudes derived from string theory [7,8]. It is recently finding application in a wide range of physical problems, including multi-loop effective actions and scattering amplitudes [3,9], constant field QED and the Schwinger effect [10,11], gravitational interactions [12,13], higher spin fields [14,15], quantum fields in non-commutative space-time [16,17] and the form factor decomposition of the four gluon vertex reported by Schubert elsewhere in these proceedings.…”
Section: Introductionmentioning
confidence: 99%